2010
DOI: 10.1243/09544119jeim799
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Evaluation of Orthopaedic Implants for Hip Fractures by Finite Element Analysis and In-Vitro Tests

Abstract: The aim of this study was to test the hypothesis that a reinforced gamma nail for the fixation of subtrochanteric fractures would experience less stress during loading compared with a common gamma nail. The issue of whether the use of the stronger implant would result in more stress shielding in the surrounding bone was also addressed. A finite element analysis (FEA) of a synthetic bone was employed to calculate the stress distribution in implant and bone for two fracture types (AO 31-A3.1 and AO 31-A3.3). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 54 publications
(57 reference statements)
2
59
0
Order By: Relevance
“…27 We did not include muscle forces. Indeed, a recent study 8 on hip fractures concluded that additional muscle loading, as suggested by Heller et al, 28 had no significant effect on the results. There are discrepancies in the values reported for the peak joint reaction forces acting on the hip.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…27 We did not include muscle forces. Indeed, a recent study 8 on hip fractures concluded that additional muscle loading, as suggested by Heller et al, 28 had no significant effect on the results. There are discrepancies in the values reported for the peak joint reaction forces acting on the hip.…”
Section: Discussionmentioning
confidence: 95%
“…Friction coefficients were taken from the literature: 0.46 for bone-bone interactions, 8 0.42 for bone-implant interactions, 9 and 0.2 for implant-implant interactions. 10 The models were subjected to a load of 1,866 N corresponding to 300% body weight (BW), in accordance with values reported for walking and stair climbing.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of real bone, a composite bone specimen has been used that possibly cannot reproduce all in-vivo conditions, precisely. However, composite bone has been successfully used in several biomechanical studies, since inter-specimen variability is small and therefore provides more consistency among specimens than cadaveric bone [29][30][31][32][33][34][35][36][37]47]. The support structure is still not entirely representative of the in-vivo situation, where there are no rigid constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods to measure strain in bone include extensometers, fiber optic sensors and non-contact strain measurements such as 3D image correlation photogrammetry (Turner and Burr 1993, Tyson et al 2002, Fresvig et al 2008). Measures of strain on the femoral cortex or the implant itself are not common in the literature dealing with fixation of hip fractures, but examples do exist (Mizrahi et al 1980, Eberle et al 2010.…”
Section: Strainmentioning
confidence: 99%
“…In other words, three screws through the femoral neck stiffens the proximal femur on which a fractured, yet fixed femoral head fragment, shows increased elastic rotations when compared to the intact state. There are few publications presenting cortical strain data from femoral neck fracture experiments and such studies have often been performed in order to validate computer models (Eberle et al 2010, Peleg et al 2010). Eberle and colleagues measured cortical strain on the proximal femur in intact cadaver specimens and after implantation of a compression hip screw (CHS) with an antirotation screw (n = 6) or a femoral neck plate (FNP) with three partially threaded screws (n = 6) in unfractured femurs (Eberle et al 2011).…”
Section: Study IImentioning
confidence: 99%